The 'difficult heritage' of the Native Mounted Police. (August 2020) - Rowse, Tim; Waterton , Emma
This article intervenes in the debate about whether and how the 'Frontier Wars' should be represented in Australia's military heritage. If they were to be represented, those who resisted British colonial occupation would figure as Aboriginal patriots in a renovated heritage of Australian service to country. We point out, however, that certain historical actors have been, so far (and perhaps forever), excluded from such a revised Indigenous military heritage: those Aboriginal peoples who 'served' in the Native Mounted Police. While the archival record is patchy, scholarship tells us that, in their pacification of frontiers, the Native Mounted Police killed many Aboriginal peoples. Interrogating the meaning of war heritage in Australia, we discuss the politics of forgetting against the obligations of historiography to collective memory and ask: must scholarship always interrogate identity-sustaining myth, in service to the truth? To explore this question, we adopt Sharon Macdonald's concept of 'difficult heritage'.